(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
The main objective of this study was to improve the inclusion formation between Ketoprofen and β-cyclodextrin and thus enhance dissolution profile and bioavailability of the ketoprofen. Solubility studies demonstrated the formation of the ketoprofen-β-cyclodextrin inclusion complex with 1:1 stoichiometry. Equimolecular ketoprofen-β-cyclodextrin solid systems were prepared and characterized by DSC, FTIR and hot stage microscopy. Modification of the release of a ketoprofen from the hydrophilic matrices using cyclodextrin complexes was evaluated. The controlled release matrix tablets for the delivery of the ketoprofen were prepared by the direct compression using hydroypropylmethyl cellulose K100M. The tablets are further evaluated for their dissolution characteristics and swelling characteristics. In vitro release results demonstrated that matrix tablets containing the ketoprofen- β-cyclodextrin (KTPF-CD) solid complex displayed faster Ketoprofen release compared to those containing a mixture of physical mixture or “free” drug. Differences in the release profile of ketoprofen from the tablets could be attributed to the presence of the polymer and β-cyclodextrin complexation. The effect of polymer on ketoprofen release can affect the drug solubility (complexation) and polymer water uptake (swelling). Higher polymer water uptake may result in higher drug solubility and diffusivity in the hydrated polymeric environment.